The Role and Involvement of Student Organizations in the Anti-Corruption Movement at Islamic Higher Education Institutions: A Case Study of STAIN Bengkalis - Misda, Asruari (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
Students, as agents of change, play a strategic role in breaking the chain of corruption through prevention and the instillation of integrity values. This study aims to analyze the role and involvement of Student Organizations (Ormawa) at STAIN Bengkalis in the anti-corruption movement, based on the competency standards of the Decree of the Director General of Islamic Education Number 5783 of 2019. This study employs a quantitative descriptive method with a saturated sampling (census) technique involving 29 student organizations as respondents. Data were collected through questionnaires and documentation, then analyzed using descriptive statistics and the Miles & Huberman interactive model. The results reveal a gradation of declining student roles from personal to systemic aspects. Individual competence (preventing oneself) is in the very high category (98.6%), followed by social competence (preventing others) at 82.8%, and lowest in the competence of detecting and reporting corruption (whistleblowing) at 75.9%. These findings indicate that the anti-corruption movement of STAIN Bengkalis students is still defensive-personal (maintaining personal piety) and not yet fully offensive-systemic (daring to challenge the system). Strengthening whistleblower protection and advocacy education is required to empower students to take an active role in eradicating corruption.